Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/gj.3777
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology, geochemistry, and Hf isotopes of mafic rocks from Dalabute ophiolitic mélange in West Junggar, Xinjiang (NW China): Implications for the magmatic source and tectonic setting

Abstract: Several Palaeozoic ophiolitic mélanges distributed in the West Junggar, Xinjiang, are remnants of the Paleo‐Asian Ocean evolution. They are important keys for studying the component, tectonic evolution, and crust–mantle interaction of the Central Asian Orogenic Belt (CAOB). This paper presents petrology, zircon U‐Pb chronology, geochemistry, and Hf isotope data of mafic rocks from the Dalabute ophiolitic mélange, West Junggar. The zircon U‐Pb chronology data of gabbro in the Dalabute ophiolitic mélange can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…For example, Zircon U-Pb dating of volcanic rocks in Baogutu and Miaoergou regions of southern West Junggar has shown that northwestward intra-oceanic subduction of Junggar oceanic plate occurred during 344-331 Ma (Buckman and Aitchison, 2004;Geng et al, 2011). The ridge subduction-related magmatism, as represented by adakitic rock, high-Mg andesites, enriched-or high-Nb basaltic rocks, charnockites, and alkali-feldspar granite (Geng et al, 2009;Tang et al, 2010;Yin et al, 2010), commenced and took place between 331 and 310 Ma and probably lasted into the latest Carboniferous (302 Ma), as evidenced by the Darbut E-MORB type basalts (Liu et al, 2009). Wu et al (2018) proposed that subduction of Junggar oceanic plate started during the Early Devonian and continued to the Late Carboniferous (310 Ma), with subsequent post-collisional tectonic processes continuing to the latest Carboniferous (302 Ma).…”
Section: Tectonic Implicationsmentioning
confidence: 99%
“…For example, Zircon U-Pb dating of volcanic rocks in Baogutu and Miaoergou regions of southern West Junggar has shown that northwestward intra-oceanic subduction of Junggar oceanic plate occurred during 344-331 Ma (Buckman and Aitchison, 2004;Geng et al, 2011). The ridge subduction-related magmatism, as represented by adakitic rock, high-Mg andesites, enriched-or high-Nb basaltic rocks, charnockites, and alkali-feldspar granite (Geng et al, 2009;Tang et al, 2010;Yin et al, 2010), commenced and took place between 331 and 310 Ma and probably lasted into the latest Carboniferous (302 Ma), as evidenced by the Darbut E-MORB type basalts (Liu et al, 2009). Wu et al (2018) proposed that subduction of Junggar oceanic plate started during the Early Devonian and continued to the Late Carboniferous (310 Ma), with subsequent post-collisional tectonic processes continuing to the latest Carboniferous (302 Ma).…”
Section: Tectonic Implicationsmentioning
confidence: 99%
“…H. Li et al (, this issue) presents petrological, zircon U–Pb geochronology, geochemical characteristics of element and Hf isotope from the Sartohay region of the Dalabute ophiolitic mélange in West Junggar. These authors found that gabbros in the Dalabute ophiolite can be divided into three groups, with the youngest age group being 307.3 ± 5 Ma.…”
Section: Western Altaidsmentioning
confidence: 99%
“…During the Carboniferous, the Junggar region was in the prearc basin stage of its tectonic evolution (Geng et al ., 2009; Liu et al ., 2009; Tang et al ., 2010, 2009; Yin et al ., 2010). Under the influences of plate convergence, plate subduction, and volcanic activity, vast thicknesses of deep-water sediments were deposited, including gravity-flow deposits.…”
Section: Introductionmentioning
confidence: 99%